China's Degraded Environment Enters A New Normal. (March 2016) - Zhang, Ke; Dearing, John A.; Tong, Shilu L.; Hughes, Terry P.
Abstract : China is undergoing unprecedented social and ecological shifts, a harbinger of similar changes that will unfold in developing nations over coming decades. Many of China's degraded environments represent a new normal. Acknowledging this reality will allow societies to make informed decisions that recognize the undervalued costs of environment degradation.